Artroplastia unicompartimental medial de rodilla combinada con reconstrucción del ligamento cruzado anterior: reporte de caso - Fallaque Ruiz, Yordhanno (2026)
This case report describes a combined surgical technique involving anterior cruciate ligament (ACL) reconstruction and medial unicompartmental knee arthroplasty (UKA) performed in a single procedure. The patient was a 54-year-old active male worker with a history of medial meniscus tear previously treated with arthroscopic surgery, who presented with persistent right knee pain and instability. Imaging studies revealed severe osteoarthritis of the posteromedial compartment associated with ACL insufficiency—a challenging scenario, particularly in young and active patients. This combined approach was indicated to simultaneously restore joint stability and compartment congruence while preserving the biomechanics of the knee. Anatomical ACL reconstruction using hamstring autografts re-established anterior stability, and cemented fixed-bearing UKA restored the mechanical axis and appropriate load distribution . At six-month follow-up, the patient achieved full range of motion (0°–120°), no extension deficit, correction of the varus deformity, and marked functional improvement (Oxford Knee Score: 46). These findings suggest that combined ACL reconstruction and UKA is an effective surgical option for selected cases of unicompartmental osteoarthritis secondary to ligamentinsufficiency. This approach allows preservation of native knee kinematics and promotes early functional recovery.